Analisis Penetapan Sektor Andalan dalam Rangka Pembangunan Pertanian Kabupaten Merauke (Pendekatan Model Input-Output) - Malik, Afrizal; Friyatno, Supena (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2010)
One of the success factors of agricultural development in region is how agricultural development planned well. Determination of leading sector is an important activity for the preparation of agricultural development planning. Investment is the driving force of economic growth. With limited government and community funds, then the efficiency and effectiveness of investments aimed at mainstay sectors or commodities. Mainstay sector is the sector that can attract and encourage other economic sectors so that all economic sectors able articulates economic growth, create employment opportunities, increase income, reduce the incidence of poverty. Without any information about where or commodity sector where appropriate to be developed, then the agricultural development plan is ineffective and inefficient as well as development targets are not achieved. The study aims to: (a) formulating criteria mainstay sector, (b) identify the mainstay sector and, (c) identify the location of the agricultural seed sector by combining the information with the results of AEZ assessment. Determination sector or commodity approach Input-Output analysis and in-overlay it with the map AEZ (Agroecological Zone) (especially for the agricultural sector). The results of the study recommends that the selection of sectors/commodity sector development policy/commodity concerned in Merauke District is highly dependent on the problems facing the region. Given the poverty and scarcity of labor is still a major problem in this area, it is advisable sector/commodity which is developed sectors/commodities that have high multiplier value but low employment multipliers. Sectors which are qualified fisheries and agriculture. Furthermore, this study suggested that local governments make investments based on the landing area map and location of the potential development of the agricultural sector each district is already available from this study.